1997
DOI: 10.1016/s1074-7613(00)80377-5
|View full text |Cite
|
Sign up to set email alerts
|

The Igα/Igβ Heterodimer on μ-Negative ProB Cells Is Competent for Transducing Signals to Induce Early B Cell Differentiation

Abstract: The immunoglobulin alpha (Ig alpha)/Ig beta heterodimer was detected on the surface of mu-negative proB cell lines in association with calnexin. The cross-linking of Ig beta on proB cells freshly isolated from bone marrow of recombination activating gene (RAG)-2-deficient mice induced a rapid and transient tyrosine-phosphorylation of Ig alpha as well as an array of intracellular proteins including Syk, PI3-kinase, Vav, and SLP-76. It also elicited the phosphorylation and activation of a MAP kinase ERK but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(101 citation statements)
references
References 108 publications
4
96
1
Order By: Relevance
“…To further define the regulatory mechanisms exerted by SHP-1, we searched for novel substrates of SHP-1 in B cells. In contrast to the report showing that SLP-76 expression is restricted to monocytes, granulocytes, and T cells [35] and pro-/pre-B cells [33,34], immunoblotting with three different anti-SLP-76 Ab and RT-PCR analysis revealed that SLP-76 is expressed in all mouse B cell lines tested and in splenic B cells. This discrepancy might be explained by differences in the detection procedure for Western blotting.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…To further define the regulatory mechanisms exerted by SHP-1, we searched for novel substrates of SHP-1 in B cells. In contrast to the report showing that SLP-76 expression is restricted to monocytes, granulocytes, and T cells [35] and pro-/pre-B cells [33,34], immunoblotting with three different anti-SLP-76 Ab and RT-PCR analysis revealed that SLP-76 is expressed in all mouse B cell lines tested and in splenic B cells. This discrepancy might be explained by differences in the detection procedure for Western blotting.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, we have previously demonstrated that dephosphorylation of BLNK by SHP-1 causes a decreased association with Nck/Nck-interacting kinase (NIK) complex, suppressed c-Jun N-terminal kinase (JNK) activation, and enhanced apoptosis [30,31]. Although we [32] and others [33,34] have previously demonstrated that SLP-76 is expressed in the mouse immature B cell line WEHI-231 and in pro-/pre-B cells, the expression and the function of SLP-76 in B cells have been largely unknown. Based on these backgrounds, we addressed questions of whether the expression of SLP-76 in B cells can be generalized and, if so, how SLP-76 regulates BCR signaling.…”
Section: Introductionmentioning
confidence: 73%
“…This finding supports the notion that Igβ has a unique ability to be expressed in a mIg‐independent manner and to form an alternative ITAM‐signaling module on the B‐cell surface. However, it has also been found that the Igα/Igβ heterodimer is expressed in an mIg‐independent manner on the surface of pro‐B cell where it may be part of a pro‐B‐cell specific signaling module (Nagata et al , 1997; Maki et al , 2000). …”
Section: Discussionmentioning
confidence: 99%
“…Crosslinking of Igβ, a signaling subunit of both pre-BCR and BCR, using monoclonal antibody recognizing extracellular portion of Igβ, predominantly induces activation of ERK (Nagata et al, 1997). Therefore ERK could be a downstream target of both pre-BCR and 8 BCR.…”
Section: The Mek-erk Pathway In Early B Cell Developmentmentioning
confidence: 99%